Crystallization and melting behaviour of polymer blends comprising polyacrylate and poly(ethylene oxide) / Sim Lai Har and Chan Chin Han - Sim, Lai Har; Chan, Chin Han (2006)
Blends of poly(ethylene oxide) (PEO) with an amorphous random copolymer, polyacrylate (PA), were prepared via solution casting. Thermal properties of the blends were investigated by differential scanning calorimetry (DSC). The existence of two glass transition temperatures (Tg) over the entire composition range of the blends suggests that the blends are heterogeneous on a macroscopic scale. Equilibrium melting temperature (Tm°) of PA/PEO blends were determined after the Hoffman- Weeks method. No systematic variation of I'm0 is detected for the blends of PA/PEO after isothermal crystallization. These results clearly show that PA/PEO blends are not miscible in the melt. Isothermal crystallization kinetics of PEO in the blends were analysed by the Avrami equation at crystallization temperature (Tc) ranging between 33 and 49 °C. The overall rate constant of isothermal crystallization (KAVU) of PEO decreases exponentially with ascending PA content. The Avrami exponent (n), determined for neat PEO and its blends at all Tcs, lie between 1.98 and 3.00, suggesting a two or three-dimensional diffusion-controlled crystal growth of PEO.